Single-channel blind equalization for GSM cellular systems. - Zhi Ding (IEEE Journal on selected areas in communications)
This paper focuses on the study of blind equalization global system for mobile communications (GSM) systems using a single antenna. In order to utilize the well-known linear system model in conventional studies of blind equalization, an equivalent baseband quadrature amplitude modulation (QAM) approximation is used for the nonlinear GMSK signal in GSM systems. Since the GMSK signal in GSM has very little excess bandwidth to warrant oversampling, a derotation scheme is developed to create two subchannels for each received GMSK signal sampled at the baud rate. Linear approximation of the GMSK signal makes the traditional QAM blind equalization system model applicable for GSM. Derotation induces channel diversity without an additional antenna and reduces the number of necessary radio frequency (RF) receivers (sensors) without increasing hardware or computational costs. Several second-order statistical and higher order statistical methods of blind equalization are adopted for GSM signals